FINDINGS FROM AN END-OF-LIFE EDUCATION INTERVENTION FOR AFRICAN AMERICAN CAREGIVERS OF RELATIVES WITH DEMENTIA. (11th November 2018) - Hart, A; Bonner, G; Suarez, M; Roberson, T; Burke, L; Steffen, A
Abstract: African-American (AA) family caregivers may have insufficient knowledge to make informed end-of-life (EOL) treatment decisions for relatives with dementia. ACT-Plan, a community-based education intervention, was conducted to enhance knowledge of dementia, cardiopulmonary resuscitation (CPR), mechanical ventilation (MV), tube feeding (TF), self-efficacy to make EOL treatment decisions, and intentions to make EOL care plans in advance. This study evaluated the efficacy of ACT-Plan compared to attention control. In a theoretically based, two-group, cluster-randomized controlled trial, AA caregivers were recruited from four similar Midwestern urban mega-churches randomized to experimental or control conditions. Each church enrolled 5 to 9 participants in 4 weekly 1-hour sessions in concurrent waves (355 total: ACT-Plan n = 171, control n = 184). Dementia, CPR, MV, and TF treatments were discussed in ACT-Plan classes. Attention control addressed health promotion topics. Participants completed assessments before the initial class, after the final class (Week 4), and Week 20. Mixed-effects regression analyses compared the groups, adjusting for cluster randomization and repeated measures. Knowledge of CPR, MV, TF, and self-efficacy to make EOL treatment decisions increased statistically in the ACT-Plan group but not the control group, whereas intentions to administer treatments decreased (Cohen's d: knowledge 0.41–0.79, self-efficacy 0.45–0.60, intention -0.81 to -0.54, all p < 0.03). Similar proportions of participant groups wrote or intended to write care plans (25% and 55%, respectively; all p > 0.40). While ACT-Plan treatments increased caregivers' knowledge and self-efficacy and decreased intentions to administer treatments, more support is needed for creating written care plans.